2010
DOI: 10.1186/1471-2458-10-527
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the number of antenatal visits in a metropolitan region

Abstract: BackgroundAntenatal care has a positive effect on pregnancy, both clinically and psychologically, but consensus about the optimal number of antenatal visits is lacking. This study aims to provide insight into the dynamics of the number of antenatal visits a woman receives. Independent effects of predisposing, enabling and pregnancy-related determinants are examined.MethodsWomen were recruited in nine clinical centres in the Brussels Metropolitan region. Antenatal care use was measured prospectively. A Poisson … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
53
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 21 publications
9
53
1
5
Order By: Relevance
“…Petrou et al [20] also observed that number of prenatal care visits were associated with increasing age. On contrary, some studies have found no association of number of visits with age [21,22].…”
Section: Discussionmentioning
confidence: 85%
“…Petrou et al [20] also observed that number of prenatal care visits were associated with increasing age. On contrary, some studies have found no association of number of visits with age [21,22].…”
Section: Discussionmentioning
confidence: 85%
“…20 A alta cobertura de realização dos procedimentos clínicos obstétricos de importância no pré-natal, e a deficiência da maioria dos serviços em planejar atividades de educação em saúde e utilizar indicadores para monitoramento interno é corroborado com os achados de Silveira et al 16 Merece destaque esta última informação uma vez que autores afirmam que o conhecimento e o acompanhamento do impacto das ações em saúde devem ser viabilizados por meio de indicadores adequados, o que implica na existência de registros locais fáceis, confiáveis e contínuos. 3 Os resultados quanto à semana de início do pré-natal apresentaram-se inferiores com achados de outro estudo em âmbito internacional 21 apontando diferenças no início da atenção entre países desenvolvidos e em desenvolvimento. Entretanto os achados encontrados podem indicar uma boa captação precoce das gestantes pelos serviços, observado pela média e mediana de início do pré-natal ainda no primeiro trimestre gestacional.…”
Section: Discussionunclassified
“…Other studies show inequalities in access to or use of antenatal care in metropolitan areas of European countries 48 and developing countries 18,46 .…”
Section: Colombian Demographic and Health Survey (N = 12373)mentioning
confidence: 98%